Analytical study of drift velocity in N-type silicon nanowires - Ismail, Razali (IEEE Explore, 2009)
The limitations on carrier drift velocity due to high-field effect and randomly velocity vector in equilibrium is reported. The results are based on asymmetrical distribution function that converts randomness velocity vectors in zerofield to streamlined one in a very high electric field. The ultimate drift velocity is found to be appropriate thermal velocity for a given dimensionality for non-degenerately doped Silicon nanowires. However, the ultimate drift velocity is the Fermi velocity for degenerately doped Silicon nanowires. Other important parameter in carrier transport phenomena, for nanoscale devices is quantum confinement effect that leads to one-dimensional behavior in silicon nanowire.